The Influence of Oxidizing Parameters on the Formation of Oxide Layer as a Precursor for the Fabrication of Carbon Fiber-Steel Laminate - Chandrashakeran, Dharmesh Kumar (IRC, 2020)
The application of fiber metal lamination has been increasing in the engineering industries such as the aerospace, automotive, construction and processing industries. Fiber metal lamination are able to provide a solution to improve metallic materials’ characteristics while improving the fibers’ properties at the same time. With high reliability and cheaper alternative to provide superior properties in material, in fabricating the fiber metal laminates, the surface of contact between the metal and the fiber is a fundamental criterion. The stability of the surface of the metallic substrate is key in avoiding delamination of the fiber metal laminate due to corrosion under insulation where the metallic surface that is bonded with the fiber are decomposed. In this paper, the influence of oxide formation on carbon steel which is a precursor to carbon fiber steel laminate surface discussed with different oxidizing parameters, which are temperature, time, heating rate and surface roughness on the formation of stable oxide layer. An optimum set of oxidizing parameter and levels are determined using the Analysis of Mean (ANOM) technique in Taguchi’s method, and the contribution of each oxidizing parameter in the formation of magnetite layer is done using the Analysis of Variance (ANOVA) method.